Quantitative psychology : The 82nd Annual Meeting of the Psychometric Society, Zurich, Switzerland, 2017 /: The 82nd Annual Meeting of the Psychometric Society, Zurich, Switzerland, 2017. (2018) - Unknown
No abstract available